Analysis of Students' Reading Difficulties of SDN Bangsa Negara East Oku in Thematic Learning - Dewi, Sri Enggar Kencana; Hidayat, Sukron; Pertiwi, Ratih Purnama; Hasanah, Nur (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This study aims to describe the difficulty of learning to read on the learning outcomes of students at SDN Bangsa Negara East OKU regarding the Health Is Important Theme in the Sub-theme of My Healthy Blood Circulation. This study uses a qualitative approach. The subjects of this study were the fifth-grade teachers and students at the SDN Bangsa Negara East OKU. Data was obtained by observation, interviews, field notes, and documentation. Data analysis techniques include data reduction, data display, and verification. The validity of the data was obtained through technical triangulation. The results of this study indicate that there are still many students who have reading difficulties. The problem of reading difficulties in SDN Bangsa Negara is also related to the lack of supporting facilities for learning, the inaccessibility of learning, material problems, motivation problems, concentration problems, learning problems when the children are not ready for the learning process or refuse to learn, so the teacher's efforts in this regard are by providing additional hours and use of varied and interesting media, paying attention to student development, motivating students who have reading difficulty in class to learn, always training and trying to learn to read for students who are still lacking fluency.